2007
DOI: 10.1111/j.1440-0960.2007.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma in organ transplant recipients: The old enemy finds a new battleground

Abstract: Population registry data and published studies have demonstrated that melanomas in the transplant population occur 1.6-2.5 times more commonly compared with the general population. Studies examining possible risk factors have suggested that in this patient population, there is an increased number of melanocytic naevi. Whether this phenomenon is aetiologically related to subsequent melanoma development is currently unclear. Only one study examined the prognosis of melanomas in this population. The Israel Penn I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Four patients had early metastatic disease and 3 died of their melanoma. These histological and evolutionary data suggest that rituximab-associated melanomas could potentially be more aggressive melanoma forms, as reported in patients with organ transplants [6]. The underlying pathology does not however seem to be a determining factor.…”
Section: Discussionmentioning
confidence: 61%
“…Four patients had early metastatic disease and 3 died of their melanoma. These histological and evolutionary data suggest that rituximab-associated melanomas could potentially be more aggressive melanoma forms, as reported in patients with organ transplants [6]. The underlying pathology does not however seem to be a determining factor.…”
Section: Discussionmentioning
confidence: 61%
“…23,24,38 All things considered, although the majority of these large population-based studies of OTRs have shown an increased risk of melanoma, the relative risk is still much lower than that of nonmelanoma skin cancers. 40,41 By comparison, the incidence of nonmelanoma skin cancers posttransplant is increased 50-to 250-fold for squamous cell carcinoma and 10-fold for basal cell carcinoma. 24,26,42 Melanoma Before Transplant The majority of research shows no strong evidence supporting an increased risk of melanoma recurrence in patients who have a history of melanoma before transplant.…”
Section: Article Highlightsmentioning
confidence: 99%
“…Some studies have documented findings about survival, metastatic potential, and other aspects of the clinical course. 6,25,47 De novo melanomas tend to develop 3 years posttransplant or later, 40 with reports ranging from 14 to 236 months. 29 The mean time for melanoma development in the OTR population is 61 months posttransplant, 44 with some studies documenting a range of 40 to 132 months.…”
Section: Clinical Course Of Melanoma In Solid Organ Transplant Recipimentioning
confidence: 99%
See 2 more Smart Citations